Cyberbullying on YouTube social media: Ria Ricis's feedback on haters - Diyanti Diyanti; Vyki Mazaya (Islamic Communication Journal, 2022)
Interactive communication in virtual space enables free and uncontrolled communication. This study aims to know the communication of Ria Ricis and the netizen and her feedback on haters. Ria Ricis is an influencer who often gets a negative response the netizen on her social media contents. This study will look at Ria Ricis feedback communication patterns on YouTube with Wilbur Schramm's theory. The data source was based on the haters' comments on a video "Ricis reaction in reading hate comments on Tiktok…Wkwk" uploaded by RICIS TV YouTube channel. The data analysis technique used data reduction, display, and conclusion. The result showed that the communication process started from some Ria Ricis posts on a TikTok account get many negative comments from the netizen. Then, there was a lot of pressure from her fans. So, she then created a YouTube video as the Ria Ricis's positive feedback for the haters.  A positive response to the haters is given to minimize the occurrence of an unhealthy communication atmosphere and to reduce endless communication conflicts. The results of this study contribute to strengthening the existence of Islamic communication principles which can become a moral basis for communication activities on social media. ***Komunikasi interaktif di ruang maya memungkinkan komunikasi yang bebas dan tidak terkendali. Studi ini bertujuan untuk mengetahui komunikasi Ria Ricis dan netizen serta tanggapannya terhadap haters. Ria Ricis merupakan salah satu influencer yang sering mendapatkan respon negatif dari netizen pada konten media sosialnya. Studi ini akan melihat pola komunikasi umpan balik Ria Ricis di YouTube dengan teori Wilbur Schramm. Sumber datanya berdasarkan komentar para haters pada video “Reaksi Ricis membaca komentar kebencian di Tiktok...Wkwk” yang diunggah kanal YouTube RICIS TV. Teknik analisis data menggunakan reduksi data, display data, dan penarikan kesimpulan. Hasil kajian menunjukkan bahwa proses komunikasi yang dimulai dari beberapa postingan Ria Ricis di akun TikTok mendapatkan banyak komentar negatif dari netizen. Kemudian, ada banyak tekanan dari para penggemarnya sehingga ia lantas membuat video YouTube sebagai tanggapan positif Ria Ricis terhadap para haters. Tanggapan positif terhadap para pembenci diberikan untuk meminimalisir terjadinya suasana komunikasi yang tidak sehat dan untuk meredam konflik komunikasi yang tidak berkesudahan. Hasil studi ini berkontribusi bagi penguatan eksistensi prinsip komunikasi Islam yang dapat menjadi basis moral bagi kegiatan berkomunikasi di media sosial.